Discovery of a Novel Inhibitor of Human Purine Nucleoside Phosphorylase by a Simple Hydrophilic Interaction Liquid Chromatography Enzymatic Assay. (17th February 2021) - Rabuffetti, Marco; Rinaldi, Francesca; Lo Bianco, Alessandra; Speranza, Giovanna; Ubiali, Daniela; de Moraes, Marcela Cristina; Rodrigues Pereira da Silva, Luiz Claudio; Massolini, Gabriella; Calleri, Enrica; Lavecchia, Antonio
Abstract: Human purine nucleoside phosphorylase ( Hs PNP) belongs to the purine salvage pathway of nucleic acids. Genetic deficiency of this enzyme triggers apoptosis of activated T‐cells due to the accumulation of deoxyguanosine triphosphate (dGTP). Therefore, potential chemotherapeutic applications of human PNP inhibitors include the treatment of T‐cell leukemia, autoimmune diseases and transplant tissue rejection. In this report, we present the discovery of novel Hs PNP inhibitors by coupling experimental and computational tools. A simple, inexpensive, direct and non‐radioactive enzymatic assay coupled to hydrophilic interaction liquid chromatography and UV detection (LC‐UV using HILIC as elution mode) was developed for screening Hs PNP inhibitors. Enzymatic activity was assessed by monitoring the phosphorolysis of inosine (Ino) to hypoxanthine (Hpx) by LC‐UV. A small library of 6‐ and 8‐substituted nucleosides was synthesized and screened. The inhibition potency of the most promising compound, 8‐aminoinosine (4 ), was quantified through K i and IC50 determinations. The effect of Hs PNP inhibition was also evaluated in vitro through the study of cytotoxicity on human T‐cell leukemia cells (CCRF‐CEM). Docking studies were also carried out for the most potent compound, allowing further insights into the inhibitor interaction at the Hs PNP active site. This study provides both new tools and a new lead for developing novel Hs PNP inhibitors. Abstract : A simple, inexpensive, direct and non‐radioactive enzymatic assay coupled to hydrophilic interaction liquid chromatography and UV detection (LC‐UV using HILIC as elution mode) has been developed to evaluate and screen human purine nucleoside phosphorylase ( Hs PNP) inhibitors. A lead compound, 8‐aminoinosine, was identified and validated through experimental and computational protocols.